О статистическом оценивании логарифмической производной меры в гильбертовом пространстве - Надарая, Э.А.; Сохадзе, Г.А.; Шаташвили, А.Д. (Кибернетика и системный анализ, 2009)
Розглянуто задачу оцінювання логарифмічної похідної мір у гільбертовому просторі в статистичному аналізі за незалежними спостереженнями. Ці оцінки мають велике значення, тому що в нескінченновимірному просторі відсутній аналог теореми Гливенка–Капеллі. За допомогою методу непараметричного оцінювання розглянута задача частково розв’язана для скінченновимірного і нескінченновимірного просторів. The problem of estimation of the logarithmic derivative of measures is considered in a Hilbert space in the framework of statistical data analysis based on independent observations. The estimates obtained are of great importance since analogues of the Glivenko–Kapelli theorem are absent in an infinite-dimensional space. Applying the nonparametric estimation method, the problem stated is partially solved for finite-dimensional and infinite-dimensional spaces.